THE MUSLIM REAWAKENING IN THE 19TH CENTURY PAK-HIND SUB-CONTINENT: AN OVERVIEW - DR. ANIS AHMAD , (Hamdard Islamicus, 2022)
The fall of Delhi in 1857 and the rise of the British colonialism to power in the subcontinent shattered the confidence and selfunderstanding of the Muslim community. Those who ruled huge territory for around eight centuries were suddenly reduced to a religious minority, observed suspiciously by the British colonialists. The question how it happened and why it happened kept the Muslims community for a while confused. But gradually it started to think how they lost their glory. During this period even some well informed and well-meaning Muslim leaders thought there was no future and it was better for them to emigrate to a more safe and peaceful place to avoid humiliation and discrimination. Muslims were politically, socially, economically, and culturally marginalized. At the same time, the Christian missionaries and orientalists started an intellectual crusade. Their main target were the sources of inspirations of Muslims namely The Holy Qur’Én and the life of the Prophet (Øal Allah-u-‘alaihe wa sallam) Missionaries as well as orientalists questioned the validity, relevance and authority of both the sources in a so called age of science and reason. Muslims’ response to this missionary and orientalist’s intellectual invasions was prompt. Scholars like Rahmanullah Keranvi, Sir Syed Ahmad Khan, Syed Amir Ali and Shibli Na‘mani, to mention only a few, responded in their own ways. Syed Amir Ali and Shibli in particular tried through an interpretation of the Muslim history, to prepare a ground for revival of Muslim thought and the community. This overview offers a few preliminary observations as a background to the Muslim awakening in the 19th century Pak-Hind sub-continent. This discussion leads us to a more detailed review of the contribution of Sayed Amir Ali and Shibli Na‘mani in the intellectual revival of Muslim thought and the Muslim community in the subcontinent.